KEANEKARAGAMAN ARTHROPODA PADA PERTANAMAN KUBIS (Brassica oleracea L.) YANG DIAPLIKASI INSEKTISIDA KIMIA DAN NABATI - Annam, Agung Chairul; Khasanah, Nur (AGROTEKBIS, 2017)
This research aimed to study the diversity of Arthropod at cabbage crop treated with organic with synthetic insecticides. This research was conducted at three cabbage crops. The first crop cultivated without insecticide (K0), the second crop was treated with 10% Calontropis gigantea (K1), and the third was treated with 5% emamektin benzoat (K2). The insecticides were applied initially at 14 days after planting, and repeated every 10 days until harvest. Observation of the Arthropod was done every one day before insecticides application. Diversity of ArthropodÂ  both, at the crops treated with organic insecticides and without treatment, were higher than those in the crop treated with synthetic insecticides. The diversity level of both treatments namely organic insecticides and control was middle while in the synthetic insecticide treatment the level was low.Â Key Word : Arthropod, Cabbage, diversity, insecticides.